2023
DOI: 10.3389/fmed.2023.1192376
|View full text |Cite
|
Sign up to set email alerts
|

Predicting omicron pneumonia severity and outcome: a single-center study in Hangzhou, China

Abstract: BackgroundIn December 2022, there was a large Omicron epidemic in Hangzhou, China. Many people were diagnosed with Omicron pneumonia with variable symptom severity and outcome. Computed tomography (CT) imaging has been proven to be an important tool for COVID-19 pneumonia screening and quantification. We hypothesized that CT-based machine learning algorithms can predict disease severity and outcome in Omicron pneumonia, and we compared its performance with the pneumonia severity index (PSI)-related clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(51 reference statements)
1
0
1
Order By: Relevance
“…Moreover, Chen et al found that natural killer (NK), CD4 + T, and CD8 + T cells in severely ill patients secreted less IFN-γ, suggesting that severe COVID-19 patients were immunosuppressed [ 29 ]. In the 90-day death group, the Lac content, white blood cell and neutrophil counts, CRP, PCT, IL-6, and d -dimer were all higher in the 90-day death group than in the survivor group (all p < 0.001), which was consistent with previous studies [ 19 , 23 ] As a product of anaerobic metabolism, lactate is considered a powerful indicator for assessing the severity of sepsis [ 30 ]. Gupta et al indicated that lactate is a key factor involved in the death of COVID-19 patients [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, Chen et al found that natural killer (NK), CD4 + T, and CD8 + T cells in severely ill patients secreted less IFN-γ, suggesting that severe COVID-19 patients were immunosuppressed [ 29 ]. In the 90-day death group, the Lac content, white blood cell and neutrophil counts, CRP, PCT, IL-6, and d -dimer were all higher in the 90-day death group than in the survivor group (all p < 0.001), which was consistent with previous studies [ 19 , 23 ] As a product of anaerobic metabolism, lactate is considered a powerful indicator for assessing the severity of sepsis [ 30 ]. Gupta et al indicated that lactate is a key factor involved in the death of COVID-19 patients [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…The dominant variants in China at the time were Omicron BA 5.2 and BF.7. In our series, 32.2% (73/227) of the patients with Omicron pneumonia died, which is much greater than the 4.2% (10/238) that Xu et al reported during the same period [ 19 ]. That study enrolled immunocompetent Omicron pneumonia patients with an average age of 71.84 ± 14.11 years, with comorbid cerebrovascular disease in 57.56% (137/238) and cardiovascular disease in 11.76% (28/238).…”
Section: Discussioncontrasting
confidence: 59%